Features of Interpersonal Interaction of Blind and Visually Impaired Youth with Student Group - Gudonis, Vytautas; Klopota, Yevhenii (Pedagogika, 2017)
The paper presents outcomes research of features of interpersonal relationships, the level of perception and motivational orientations interaction of those who can see with blind and visually impaired students of higher educational institution. The attention is focused on the specifics of the social and psychological training as a means of improving communicative competence of blind and visually impaired students and optimization of their social status in the student body.